Experimental investigation on thermal conductivity of nanoparticle dispersed paraffin (NDP). (2021) - Manoj Kumar, P.; Anandkumar, R.; Mylsamy, K.; Prakash, K.B.
Abstract: This paper investigates the amendment of thermal conductivity of the commercial grade paraffin while adding various weight percentages of Si3 N4 nanoparticles in it. The paraffin has been synthesized with four different weight percentages of nano-Si3 N4 particles that are 0.5%, 1.0%, 1.5% and 2.0% of weight, respectively. The surface morphology of the prepared samples was analyzed with the aid of field emission scanning electron microscope. The size of the nanoparticles was validated using particle size analyzer. Thermal conductivity of the samples were measured with the help of thermal properties analyzer. The results evidenced that the diffusion of the nanoparticles is uniform inside the paraffin matrix and nano-Si3 N4 particles greatly improved the thermal conductivity of the base paraffin. Nevertheless, the improvement is non-linear with respect to the upsurge in weight percentage of nano-Si3 N4 particles. The paraffin upto 1.0 wt% of nano-Si3 N4 particles found to show the substantial improvement comparing with 1.5% and 2.0% in weight of nano-Si3 N4 particles in paraffin.